Hydrogen storage on fullerenes: Hydrogenation of C59N using C60H36 as the source of hydrogen - Vasil’ev, Yu; Hirsch, Andreas; Taylor, Roger; Drewello, Thomas (Chemical Communications, 2004)
CH has been used as the source of hydrogen for the in situ hydrogenation of (CN), leading to C NH as the main reaction product identified by negative-ion mass spectrometry and providing evidence of the usage of C as a storage device for hydrogen.